Plan estratégico y su incidencia en la gestión de ventas de la empresa CADEPAN, periodo 2015-2019 - Haiman Zamora, Vanessa Virgnia (2016)
Due to the fact that nowadays it is important for companies to have efficient changes, this research is conducted on the basis of the information provided by CADEPAN Company. The strategic plan -the key pillar of any organization- was conducted to improve the processes that are performed in each Company area. The SWOT Analysis, (Strengths, Weaknesses, Opportunities, Threats) was conducted for the correct functioning of the strategic plan. In other words, an internal and external company’ study. With SWOT Analysis, CADEPAN Company could discover it real economic and financial situation. In my research I used the Inductive Method, documentaries, the interview to the Manager of the Company and conducted surveys to the inhabitants of Santo Domingo de los Tsáchilas, for getting accurate information. At the end of this research, it was concluded that the company does not has a strategic plan for it development. Was necessary SWOT agreed raise the same methods and programs to achieve meet the objectives of this study analysis. These plans are the most remarkable; training vendors , make a strategic plan , improve product marketing and raise consumer policies and incentives . KEY WORDS: Strategic plan, quality, service, sales.